Ideologi Politik dalam Khazanah Penafsiran: Ayat-ayat Legitimatif al-Qur’ān pada Kasus Suksesi Abū Bakr al-Ṣiddīq - Baihaki Baihaki (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2019)
Abstract: The study focuses on the discussion of a political polemic which has led to theological disputes and has subsequently created various types of interpretations of the Qur’ān. In this context, the author limits the discussion into three main treasures, namely Sunnī, Shī‘ah, and Mu‘tazilah. The polemic commenced due the succession process of Abu Bakr’s caliphate. It has been known that the Sunnī group claimed Abu Bakr as the successor of the Prophet Muhammad, while the Shī‘ah people demanded ‘Alī b. Abī Ṭālib as the one who possesses right to be the successor of the Prophet. Different political affiliation has consequently led to different interpretations of the Holy texts produced by these different groups. It is, therefore, interesting to observe how the similar Qur’anic verses are interpreted differently. Comparing inter-stream interpretations of the Qur’ān will show us the difference and contestation of meaning among them. This article will demonstrate how an interpreter of al-Qur’ān has been always influenced by the context of his/her historical background and expertise, including the political ideology he or she affiliated to.